Solidary economy and SDG 8: Perspectives and interrelations - Almeida Souza, Julliermy Luan de; Vasconcelos , Ana Cecília Feitosa de; Ernesto Lopes, Mariangela Vasconcelos (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: This study aims to analyze how the Solidary Economy Fair, organized by a public Higher Education Institution located in Campina Grande, Paraíba, contributes to achieving Sustainable Development Goal (SDG) 8, which seeks to promote sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all. Methodology/Approach: A qualitative, exploratory research. Data collection was carried out through semi-structured interviews with participants of the fair, and the data were analyzed based on the content analysis technique of the interviewees' responses. Originality/Relevance: This study is original in empirically investigating the relationship between solidary economy and sustainable development from the perspective of the solidarity fair, demonstrating its contributions to achieving SDG 8. Principal Results: The results reveal that the Solidary Economy Fair contributes positively to achieving SDG 8. The actions promoted include creating strong and supportive networks, job and income generation, and providing decent and productive work. These results offer valuable insights for new public policies and sustainable development strategies at regional and national levels. Theoretical/Methodological Contributions: The study contributes by expanding scientific discussions on the impact of the solidary economy on sustainable development. It also offers a robust methodological approach that can be applied in other contexts to evaluate local initiatives aligned with the SDGs. Furthermore, it emphasizes the importance of initiatives such as the Solidary Economy Fair for strengthening public policies and regional strategies for sustainable development.